2006
DOI: 10.1001/archpedi.160.6.573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regular Physical Activity on Control of Glycemia in Pediatric Patients With Type 1 Diabetes Mellitus

Abstract: In pediatric patients with type 1 diabetes mellitus, frequency of RPA is a major factor influencing the control of glycemia without increasing the risk for severe hypoglycemia. Regular physical activity should be recommended in pediatric patients with type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 27 publications
(40 reference statements)
8
103
0
7
Order By: Relevance
“…This comes with Herbst et al [16] who studied the relation between frequency of RPA and glycemic control and revealed that HbA1c level was higher in the groups with less frequent RPA ( 8.4% in group RPA0 vs. 8.1% in group RPA2). Also, he stated that multiple regression analysis revealed RPA was one of the most important factors influencing glycemic control which comes with our results.…”
Section: Discussionmentioning
confidence: 60%
“…This comes with Herbst et al [16] who studied the relation between frequency of RPA and glycemic control and revealed that HbA1c level was higher in the groups with less frequent RPA ( 8.4% in group RPA0 vs. 8.1% in group RPA2). Also, he stated that multiple regression analysis revealed RPA was one of the most important factors influencing glycemic control which comes with our results.…”
Section: Discussionmentioning
confidence: 60%
“…The use of different methods of assessing PA and/or small study populations might explain the conflicting results. One of the studies that revealed a statistically significant correlation between physical activity and HbA1c is a large German cross-sectional questionnaire study (6).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on the correlation between physical activity and HbA1c. Some have succeeded in showing a significant HbA1c-lowering effect of physical activity (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), whereas others have failed do so (16)(17)(18)(19)(20)(21)(22). HbA1c is a main variable in pediatric diabetes care.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do risco de hipoglicemia, a AF é recomendada para crianças com DM1 47,48 . Segundo Hoffman 49 , com um regime adequado de insulina e com um plano alimentar individualizado, crianças com DM1 podem usufruir dos benefícios físicos e psicossociais promovidos pelo exercício.…”
Section: O Medo Da Hipoglicemiaunclassified
“…Herbst et al 47 relataram que a AF regular é o fator que mais influencia o controle da glicemia sem, no entanto, aumentar o risco de hipoglicemia em crianças com DM1. Da mesma forma, alguns estudos têm comprovado que a AF regular, seja ela contínua ou intermitente 41,66,73 , não aumenta o risco de hipoglicemia 13 .…”
Section: O Esporte E a Criança Com Diabetes Tipounclassified